FORMULATION OF BREADFULNESS LEAF EXTRACT GRANULES (Artocarpus altilis) USING THE WET GRANULATION METHOD - Rahayu, Feronika Evma; Salwa, Annisa Nurhidayah; Putriani, Dini; Pratiwi, Ditha Arum; Putri, Elma Triana; Marsella, Marsella; Putri, Nuraeni Fadhila Dwi; Syaifa, Syifa Putri Nabila Nur (STIKes Medistra Indonesia, 2025)
Breadfruit (Artocarpus altilis) is a local fruit that has high productivity because it is spread in various regions, especially Indonesia. Parts of the breadfruit plant can be utilized as medicine. One of the developments of breadfruit leaves is the manufacture of granules. Granule is a product resulting from the granulation process which will then be used as a tablet preparation. The purpose of this study was to design and evaluate breadfruit leaf extract in granule form as a preparation that is practical, stable, and effective in providing therapeutic benefits derived from the bioactive content of breadfruit leaves. The method used in this research is experimental. The results of the physical characteristics of the water content test obtained a value of 4%, the stationary angle test obtained a value of 24 °, the flow velocity test obtained a value of 2.72 grams / second, the compressibility test obtained a value of 20%. It can be concluded that the test results of the physical characteristics of the granule and the granule physical stability test meet the requirements.